Empirical Examination of the Prospects and Challenges of the State Policing System in Nigeria - Ikubanni, Oluwaseye Oluwayomi; Adeboye, Oluwaseye Thompson; Oyebade, Alade Adeniyi; Oyebanji, Aderemi Olubunmi (Universitas Muhammadiyah Tangerang, 2024)
The rising insecurity in Nigeria has cast doubt on the effectiveness of the Nigerian Police Force, which operates under the control of the federal government. This has led to calls for the decentralization of policing powers to the states as a possible solution to addressing the security challenges. This study investigates the prospects and potential challenges of implementing a state policing system in Nigeria, using both doctrinal and non-doctrinal research methods. A descriptive and analytical approach was applied to interpret empirical data gathered from 1,051 questionnaires distributed to randomly selected respondents. The findings indicate that the current centralized structure of the Nigerian Police Force is inadequate for ensuring public safety. Additionally, the synthesis of the data shows that state policing holds significant potential for effectively combating insecurity in Nigeria, although issues such as corruption and lack of funding remain significant obstacles. The study concludes by recommending reforms to the existing legal framework to allow for the decentralization of policing in Nigeria.Keywords: Policing, Insecurity, State Policing, Nigerian Police Force, Police and Security